2013
DOI: 10.1039/c3cc41383g
|View full text |Cite
|
Sign up to set email alerts
|

Micro-flowers changing to nano-bundle aggregates by translocation of the sugar moiety in Janus TA nucleosides

Abstract: We designed and synthesized the Janus-type TA nucleosides (1-3) by using a transglycosylation protocol. Surprisingly, the subtle translocation of the ribose from N8 to N1 by about 230 pm in space leads to the formation of entirely different shaped superstructures, micro-flowers for J-AT and nano-bundles for J-TA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Finally, we followed an unusual transglycosylation following our previous synthesis of N1-glycosylated ribosyl AT nucleoside to obtain the N1-isomer successfully [22]. Comparing these three isomers, compound 1 and 2 have the similar, and compound 3 has a distinct electronic configuration on the fused ring system: the former two have a similar structure like alloxazine form, and the latter one has the isoalloxazinic form of pteridine derivatives.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Finally, we followed an unusual transglycosylation following our previous synthesis of N1-glycosylated ribosyl AT nucleoside to obtain the N1-isomer successfully [22]. Comparing these three isomers, compound 1 and 2 have the similar, and compound 3 has a distinct electronic configuration on the fused ring system: the former two have a similar structure like alloxazine form, and the latter one has the isoalloxazinic form of pteridine derivatives.…”
Section: Resultsmentioning
confidence: 98%
“…Theoretically, then the AT pyrimido [4,5-d]pyrimidine nucleoside system can also form either one of this base air motif. Interestingly, our previous researches showed that for the AT pyrimido [4,5-d]pyrimidine system, the reverse Watson-Crick seemed to be the more preferred base pair motif, and its existence was firmly confirmed by several N8 glycosylated Janus-type AT nucleosides single crystals X-ray analysis [22,23]. However, according to our previous studies the glycosylation position and the configuration of sugar residue have profound effects on the base pair patterns for AT pyrimido [4,5-d] pyrimidine system.…”
Section: Solid State Structurementioning
confidence: 90%
See 1 more Smart Citation
“…NAs are capable of self‐assembling in both solution and the dry state. In solution, NAs and their derivatives can self‐assemble into helices, vesicles, hydrogels, ribbons, nanotubes, and flowers . In dry environments, and in particular on an Au (111) substrate, racemic DHPA, self‐assemble into long and well‐organized noncovalent supramolecular polymers .…”
Section: Introductionmentioning
confidence: 99%
“…They are also becoming increasingly important in nanotechnology due to their ability to self‐assemble in both aqueous and dry environments. In aqueous environments, NAs and derivatives have been found to self‐assemble into helices, vesicles, hydrogels, ribbons, nanotubes, and flowers . In dry environments, and in particular on a Au(111) substrate, the molecule N(9)‐(2,3‐dihydroxypropyl Adenine) (DHPA, Figure a,b), which is a NA of adenosine, was found to self‐assemble into a 100 nm long and well‐organized supramolecular polymer .…”
Section: Introductionmentioning
confidence: 99%